How Old Are the Platonic Solids? - Lloyd, David R (The Best Writing on Mathematics 2013, 2014)
Recently a belief has spread that the set of five Platonic solids has been known since prehistoric times, in the form of carved stone balls from Scotland, dating from the Neolithic period. A photograph of a group of these objects has even been claimed to show mathematical understanding of the regular solids a millennium or so before Plato. I argue that this is not so. The archaeological and statistical evidence do not support this idea, and it has been shown that there are problems with the photograph. The high symmetry of many of these objects can readily be explained without